2017
DOI: 10.1001/jamasurg.2016.4981
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Incentive Spirometry on Postoperative Hypoxemia and Pulmonary Complications After Bariatric Surgery

Abstract: clinicaltrials.gov Identifier: NCT02431455.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 26 publications
0
32
0
1
Order By: Relevance
“…In 2017, Pantel et al 38 reported the results of a randomized clinical trial that compared the use of postoperative IS to no use of IS after bariatric surgery. Postoperative IS did not demonstrate any effect on postoperative hypoxemia or postoperative pulmonary complications.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…In 2017, Pantel et al 38 reported the results of a randomized clinical trial that compared the use of postoperative IS to no use of IS after bariatric surgery. Postoperative IS did not demonstrate any effect on postoperative hypoxemia or postoperative pulmonary complications.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…A 2017 singlecenter randomized controlled trial that compared IS to no IS found no difference in the development of postoperative hypoxemia and pulmonary complications after bariatric surgery. 17 A systematic review of PEP therapy administered after abdominal surgery identified only 4 randomized controlled trials, all published before 1993, conducted with PEP therapy in subjects who had abdom-inal surgery. 18 One study revealed positive differences; a higher P aO 2 on days 2 and 3, and a lower incidence of atelectasis at day 3.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, incentive spirometers are easy to use and there is the possibility of using it independently after the previous training as well as a visual feedback that allows a patient to record obtained LIC indicators yourself. Howe ver, there is another opinion on the effectiveness of the IS, as Pantel H. et al (2017) [12] did not reveal any influence of the IS on the postoperative pulmonary complications development in patients after bariatric surgery, therefore its use is not recommended for this category of patients. Paulo do Nascimento Junior et al (2014) [13] reviewed the data from 12 studies published before August 2013 and concluded that there was low quality evidence regarding the lack of effectiveness of incentive spirometry for prevention of postoperative pulmonary complications in patients after upper abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Incentive spirometry (IS) is a lung expansion technique, which stimulates maximum inspiratory effort with the aim of the most complete filling of the alveoli with air providing a slow maximal inspiration. However, there are contradictory data on the use of IS effectiveness for PPCs prevention in patients after upper abdominal surgery [9][10][11][12][13][14][15].…”
Section: ключові словаmentioning
confidence: 99%